Analisis Tindakan Rasis Dalam Film Thailand “A Little Thing Called Love” - Vitaloka, Feby; Narti, Sri; Putra, Dilmai (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Film is a powerful artistic medium in society, serving as a source of entertainment, education, and shaping social perspectives through audio-visual experiences. *A Little Thing Called Love*, a Thai film directed by Puttipong Pormsaka Na-Sakonnakorn and Wasin Pokpong, tells the story of a girl named Nam who struggles to gain the attention of Shone, the popular student at her school. The film highlights issues of racism and beauty standards. This study aims to explore the racist actions depicted in the Thai film *A Little Thing Called Love*. The research method used is descriptive qualitative, with data collection techniques through observation and documentation. The theoretical framework employed is Roland Barthes’ semiotic analysis, which is used to examine the representation of racism and beauty standards in the film, particularly through denotation, connotation, and myth as reflected in the characters and storyline. The findings of this study indicate that *A Little Thing Called Love* delivers layered messages through semiotic analysis at the denotative, connotative, and mythic levels. Dialogues like "Dasar Hitam!" at 06:51 reflect racial bias and social pressure regarding beauty standards, impacting Nam's self-esteem. At 35:15, the dialogue "Mereka semua jelek" highlights the social grouping dynamics based on appearance, while the dialogue at 35:57, "Jika tidak yakin kalau cantik, bisa ke klub yang lain," emphasizes expectations regarding physical beauty. The climax at 1:51:56 portrays Nam’s transformation into a confident individual, conveying the message that a person’s worth lies in their achievements and self-confidence, not just their appearance